Surgery for sleep-disordered breathing - Hörmann, Karl; Verse, Thomas (Springer, 2005)
In recent years, the spectrum of therapy for sleep-related breathing disorders has been immensely enriched by numerous innovative surgical procedures and techniques. Deciding which therapy is most appropriate for which patient is often a difficult matter, especially in light of the non-surgical alternatives. This book analyses the efficiency of the recognised surgical procedures; it is rooted in evidence-based medicine. Indications, techniques, complications, and specific follow-up treatments in the realm of sleep medicine have been compiled in the form of a primer. The authors are directors of one of the largest otolaryngological sleep laboratories in the world and perform approximately 1,500 surgical sleep medicine procedures per year. The complete surgical and sleep medicine know-how of the authors, as well as the experience of numerous international courses on sleep surgery, have been incorporated into this volume. It is therefore the fundamental textbook for sleep medicine surgeons
Includes bibliographical references (p. [137]-158) and index
Keywords: Schlafapnoe; Chirurgie